Characterization of Salmonella Typhimurium and its monophasic variant 1,4, [5],12:i:- isolated from different sources - Proroga, Yolande Therese Rose; Mancusi, Andrea; Peruzy, Maria Francesca; Carullo, Maria Rosaria; Montone, Angela Michela Immacolata; Fulgione, Andrea; Capuano, Federico (Folia microbiologica, 2019)
In order to characterize the most commonly detected Salmonella serotypes, we tested 124 isolates of S. Typhimurium and 89 isolates of the monophasic variant of S. Typhimurium (S. 1,4, [5],12:i:-) for their antimicrobial susceptibility by means of the Kirby-Bauer disk-diffusion method, and for the detection of 19 genes (four Phage Markers (g13, Sieb, eat, g8), ten prophage-related virulence genes (gipA, gtgB, nanH, gogB, grvA, sopE, sspH1, sspH2, sodC1, gtgE), and five plasmid-borne virulence genes (spvC, pefA, mig5, rcK, srgA)) by means of PCR-based assays. A total of 213 strains were analyzed from, humans (n = 122), animals (n = 25), food (n = 46), and irrigation water (n = 20). S. Typhimurium isolates showed higher variability, in both their resistance profiles and molecular typing, than S. 1,4, [5],12:i:-. Strains from irrigation water displayed significantly higher susceptibility to antibiotics than those from the other sources. Resistance to ampicillin, streptomycin, sulfonamide, and tetracycline was the most commonly detected resistance profile (R-type), being in serovar S. 1,4, [5],12:i:-, frequently associated to resistance to other antimicrobials. Significant differences in genetic profiles in the two abovementioned Salmonella serotypes were found. None of the plasmid-borne virulence genes investigated were detected in S. 1,4, [5],12:i:- isolates, while those genes, characterized 37.9% of the S. Typhimurium strains. Differences in the prevalence of some molecular targets between the two Salmonella serotypes deserve further study. Importantly, the grvA gene was found exclusively in S. Typhimurium strains, whereas sopE, sodC, gtgB, and gipA were mainly detected, with a statistically significant difference, in S. 1,4, [5],12:i:- isolates.
Keywords: Virulence; Animals; Food Microbiology; séroskupina; Molecular Typing; mikrobiální testy citlivosti; salmonelóza; Salmonella Infections; bakteriální geny; lidé; Anti-Bacterial Agents; molekulární typizace; Prophages; Genetic Variation; virulence; potravinářská mikrobiologie; Salmonella typhimurium; Microbial Sensitivity Tests; plazmidy; mnohočetná bakteriální léková rezistence; profágy; Drug Resistance, Multiple, Bacterial; Genes, Bacterial; Water Microbiology; Plasmids; zvířata; mikrobiologie vody; antibakteriální látky; genetická variace; Serogroup; Humans